Hotspots of recent hybridization between pigs and wild boars in Europe. Issue 1 (December 2018) - Iacolina, Laura; Pertoldi, Cino; Amills, Marcel; Kusza, Szilvia; Megens, Hendrik-Jan; Bâlteanu, Valentin; Bakan, Jana; Cubric-Curic, Vlatka; Oja, Ragne; Saarma, Urmas; Scandura, Massimo; Šprem, Nikica; et al.
Abstract After a strong demographic decline before World War II, wild boar populations are expanding and the species is now the second-most abundant ungulate in Europe. This increase raises concerns due to wild boar impact on crops and natural ecosystems and as potential vector of diseases. Additionally, wild boar can hybridize with domestic pigs, which could increase health risks and alter wild boar adaptive potential. We analysed 47, 148 Single Nucleotide Polymorphisms in wild boar from Europe (292) and the Near East (16), and commercial (44) and local (255) pig breeds, to discern patterns of hybridization across Europe. We identified 33 wild boars with more than 10% domestic ancestry in their genome, mostly concentrated in Austria, Bosnia and Herzegovina, Bulgaria and Serbia. This difference is probably due to contrasting practices, with free-rangingvs . industrial farming but more samples would be needed to investigate larger geographic patterns. Our results suggest hybridization has occurred over a long period and is still ongoing, as we observed recent hybrids. Although wild and domestic populations have maintained their genetic distinctiveness, potential health threats raise concerns and require implementation of management actions and farming practices aimed at reducing contact between wild and domestic pigs.